2016
DOI: 10.3138/ptc.2015-58
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise on Patients with Guillain-Barré Syndrome: A Systematic Review

Abstract: Purpose: To evaluate the effects of exercise interventions on improving physical outcomes in patients with Guillain-Barré syndrome (GBS). Methods: The PubMed database was searched for articles published up to and including February 2015. Randomized controlled trials (RCTs), case reports, and quasiexperimental and single-subject designs published in English-language, peer-reviewed journals that assessed the impact of physical exercise on patients with GBS were included; study quality was assessed using Sackett'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
0
21
0
3
Order By: Relevance
“…The intensity was consistent with the functional capabilities of the cardiovascular system, which required a three-fold heart rate and arterial blood pressure measurement during the session performance, as well as the appearance of rapid fatigue in GBS patient (Arsenault, 2016…”
Section: Interventionmentioning
confidence: 91%
“…The intensity was consistent with the functional capabilities of the cardiovascular system, which required a three-fold heart rate and arterial blood pressure measurement during the session performance, as well as the appearance of rapid fatigue in GBS patient (Arsenault, 2016…”
Section: Interventionmentioning
confidence: 91%
“…Garssen et al reported that physical exercise not only significantly reduces fatigue, but also relieves anxiety and depression [38]. The implementation of a tailor-made exercise programme reduces fatigue in GBS patients by 20% [4,38]. Although physical fitness itself reduces fatigue levels and improves mental functioning, exercise also improves fatigue independent of the patient's physical fitness level [29,38].…”
Section: A Multidisciplinary Team Approach For the Management Of Gbsmentioning
confidence: 99%
“…Conflicting reports have suggested that not all GBS patients have favourable responses to exercise [45,46]. A lack of improvement in residual fatigue may not be easy to rationalise, due to the absence of an underlying pathophysiological mechanism (such as nerve dysfunction, anaemia, hypothyroidism, diabetes, or chronic illness) [7,30].…”
Section: A Multidisciplinary Team Approach For the Management Of Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Различные типы упражнений позволяют улучшить физическое состояние пациента (увеличение мышечной силы, улучшение функций сердечно-легочной системы), а также снизить общую слабость и патологическую утомляемость [29]. Выбор вида реа-билитационного лечения зависит от выраженности неврологического дефицита, сопутствующей патологии и психического состояния пациента.…”
Section: обсуждение и обзор литературыunclassified